The mediating role of academic stress on the effects of self-regulated learning and smartphone addiction on academic procrastination - Salsabila Salsabila; Diana Mutiah (Universitas Ahmad Dahlan, 2026)
Self-regulated learning is typically conceptualized as a protective factor against academic procrastination. However, its role may be more complex in high-demand academic contexts such as undergraduate thesis completion. This study investigated the direct and indirect effects of self-regulated learning and smartphone addiction on academic procrastination, with academic stress as a mediator, thereby integrating three constructs that have rarely been examined within a single model among final-year students. A cross-sectional design was applied to a purposive sample of 315 final-year undergraduate students in the Greater Jakarta area. Participants completed the Tuckman Procrastination Scale (TPS), the College Student Self-Regulated Learning Scale, the Smartphone Addiction Inventory, and the Academic Stress Inventory (ASI). Path analysis was conducted to test the hypothesized relationships. Contrary to conventional assumptions, self-regulated learning showed a significant positive association with academic procrastination (β = .206), suggesting that heightened self-regulation may co-occur with maladaptive processes such as perfectionism and overplanning. Moreover, self-regulated learning exerted a significant indirect effect on procrastination through academic stress (β = −.213). Smartphone addiction was also positively associated with academic procrastination (β = .172), but this effect was not mediated by academic stress. These findings refine theoretical accounts of self-regulated learning by highlighting its context-dependent effects and underscore the distinct role of smartphone addiction in academic procrastination.